2017
DOI: 10.1002/celc.201701226
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐ and Iron‐Incorporated α‐Co(OH)2 Ultrathin Nanosheets as an Efficient Oxygen Evolution Catalyst

Abstract: Electrochemical water splitting is a critical technology for various energy storage and conversion devices, but it is greatly restricted by the sluggish kinetics of the oxygen evolution reaction (OER). Herein, an effective electrocatalyst of boron-and iron-incorporated a-Co(OH) 2 (B-a-Co 5.8 Fe LDH)ultrathin nanosheets was synthesized for the OER by using sodium tetraphenylborate (NaTPB) as a mild alkali and boron source in ethylene glycol/water system (EG-W). Benefiting from the large accessible surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Recently, a large number of experiments have suggested that many electrocatalysts show better activity after being doped with many common heteroatoms (nonmetal atoms: F, O, S, N, P, B, and metal atoms Fe, Co, Ni, Cu, Mn, Zn, etc. ). ,, In this chapter, we mainly summarize the influence of catalytic activity about metal and nonmetal heteroatomic dopants.…”
Section: Intrinsic Defects For Her and Oermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a large number of experiments have suggested that many electrocatalysts show better activity after being doped with many common heteroatoms (nonmetal atoms: F, O, S, N, P, B, and metal atoms Fe, Co, Ni, Cu, Mn, Zn, etc. ). ,, In this chapter, we mainly summarize the influence of catalytic activity about metal and nonmetal heteroatomic dopants.…”
Section: Intrinsic Defects For Her and Oermentioning
confidence: 99%
“…Except for the single species of heteroatom doping, multiple heteroatoms were also explored by researchers in water splitting. For instance, Liu and co-workers also prepared a boron and iron contemporary-doped Co-base catalyst, which was synthesized by using sodium tetraphenylborate (NaTPB) as a mild alkali and boron source in an ethylene glycol/water system. Sun and co-workers synthesized N, P, and F tridoped CoFe 2 O 4 with specifically an ionic liquid as a dopant, which is a new way for doping heteroatoms.…”
Section: Intrinsic Defects For Her and Oermentioning
confidence: 99%
“…10,31 Co 2p 3/2 has a red shi of 0.3 eV with the coated Au on Co(OH) 2 NSs. The increased Co 3+ /Co 2+ ratio in Au-Co(OH) 2 NSs demonstrates that Au coating increases the Co valence in Co(OH) 2 , which was resulting from the low coordinated Co-O bonding because of the appearance of Au.…”
mentioning
confidence: 99%
“…Fe 1 Co 1 O x ANSs possess an overpotential of ca. 240 mV, which is better than other MCoO x ANSs ( Table S1 ) and the state-of-art Co-based OER catalysts ( Table S2 ) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The higher mass activity shows the lower cost of OER catalysts in practical applications.…”
Section: Resultsmentioning
confidence: 86%
“…The Co feed amount in these materials is 0.4 mmol; Table S1: Parameter of electrocatalysts for OER in 1 M KOH; Table S2: Collection of reported Co-based electrocatalysts on glassy carbon electrode for OER in 1 M KOH. References [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%